Implementation of an intelligent manufacturing system - Li, Yu Min. (2008)
This dissertation presents an analysis of a part tracking system in an oil drill manufacturing process, using structural system analysis method. It also presents a design and implementation of an intelligent automatic tracking system to facilitate Just-In-Time (JIT) manufacturing.